2003
DOI: 10.1002/mc.10155
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the transformed phenotype and induction of differentiation‐like characteristics in cultured ovarian tumor cells by chronic treatment with progesterone

Abstract: Epidemiological evidence suggests that elevated levels of the pregnancy hormone progesterone might play a role in the reduced risk of women to develop ovarian cancer. In vitro studies have supported this hypothesis by demonstrating negative effects of this hormone on the growth and proliferation of cultured ovarian carcinoma cells. However, little is known about the underlying molecular processes and how progesterone might decrease the risk for ovarian tumors. Therefore, we investigated the effects of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…First, EDD plays a pivotal role in the progesterone pathway, being both regulated by progestin and directly binding the progestin receptor and enhancing its transcriptional activity (Callaghan et al, 1998;Henderson et al, 2002). It has been known for several years that progesterone has a protective effect on ovarian cancer, the mechanism attributed to a reversal of the transformed phenotype including reduction of cyclin-dependent kinase activity and increased Fas/FasL-induced apoptosis (Blumenthal et al, 2003;Syed and Ho, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…First, EDD plays a pivotal role in the progesterone pathway, being both regulated by progestin and directly binding the progestin receptor and enhancing its transcriptional activity (Callaghan et al, 1998;Henderson et al, 2002). It has been known for several years that progesterone has a protective effect on ovarian cancer, the mechanism attributed to a reversal of the transformed phenotype including reduction of cyclin-dependent kinase activity and increased Fas/FasL-induced apoptosis (Blumenthal et al, 2003;Syed and Ho, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by studies in MDA-MB-231 breast cancer cells lacking both ER and PR, in which RU-38486 retained its antiproliferative activity [14]. On the other hand, our laboratory using SK-OV-3 cells [18] and others using SV-40 transformed ovarian cystadenoma cells [51] have shown that RU-38486 elicits progesterone-like effects in terms of growth inhibition although with greater potency than progesterone, whereas others [52] using HOC-7 ovarian carcinoma cells demonstrated that high concentration (30 μM) progesterone stimulates p21 cip1 and p27 kip1 expression and inhibit Cdk-2 activity mimicking our observations with antiprogestins. Whether progesterone and antiprogestins share similar mechanism of action when acting as anti-proliferative agents, and which are their downstream targets, need to be investigated to identify the genetic background of ovarian cancers required for susceptibility to growth inhibition by antiprogestins.…”
Section: Discussionmentioning
confidence: 87%
“…Pretreatment with progesterone has been shown to reduce the number of tumor implants and metastases, thus prolonging the animal life span (46). Additionally, long-term progesterone treatment of ovarian cancer cells was able to suppress the transformed phenotype as indicated by the acquisition of contact inhibition and loss of anchorage-independence (48). Our observations of decreased tumor growth in the progestin treated arms validate these findings in the literature and could serve as an explanation for the protective effect of progesterone in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%